Curriculum Of Kitab Kuning Learning Base On Integrative Approach/ منهج تعليم كتب التراث على ضوء المدخل التكاملي - Slamet Daroini; Mohammad Atmim Aisyi (Ijaz Arabi Journal of Arabic Learning, 2022)
This study aims to describe and analyze: objectives, materials, methods, and assessment of Kitab Kuning learning with an integrative approach. This study originated from students assumption that difficult to study Kitab Kuning because it requires good reading skills and mastery of language rules. Kitab Kuning learning at Islamic boarding school was not effective due to decreased interest, quality and competence of students in reading Kitab Kuning. Only a few educational institutions under Islamic boarding school whose study Kitab Kuning is effective. This study uses a qualitative approach and descriptive analysis methods. Data collection observation, interviews, and documentation. Data analysis was performed using interactive analysis. Data validity test was done by triangulating source. This study’s results are: Objectives of Kitab Kuning learning with integrative approach are to build a scientific environment in developing Islamic scientific tradition at elementary-middle level; increasing quality and quantity of competent students in reading Kitab Kuning; preparing room heads cadre who are competent in guiding students in Islamic scholarship especially in guidance Kitab Kuning; and preparing cadres of Ma'had ʻAly Salafiyah Syafi'iyah Sukorejo Situbondo. The materials are al-Qur'an/Tajwid, Nahwu, Sharraf, Mantiq, Balaghah, Fiqh, Fiqh Ibadah, Fiqh al-Qur'an, Methodic Fiqh, Thematic Fiqh, Usul Fiqh, Qawa'id Fiqh, Akhlaq, Tawhid, and BMK. The methods are discussion method, bandongan method, lecture method, question and answer method, and problem solving method/bahtsul masail. The assessments are entrance test, formative and summative, and knockout assessment.